Posteromedial elbow dislocation with lateral humeral condylar fracture in children: Three case reports and a literature review. Issue 36 (September 2018) - Tomori, Yuji; Nanno, Mitsuhiko; Takai, Shinro
Abstract: Rationale: Posteromedial dislocations of the elbow with lateral humeral condylar fractures (LCFs) are uncommon, and only isolated cases have been reported in the English-language literature. Because of the complex radiolucent cartilaginous structures and late-appearing ossification centers, radiological diagnosis of elbow dislocations with LCF in children is challenging. Patient Concerns: We report three children with posteromedial elbow dislocation: two patients with Milch type I and one patient with Milch type II LCF. Diagnoses: In our report, radiographs showed only a small bone fragment, and arthrography or computed tomography were helpful diagnostic aids in cases 1 and 3. In contrast, the patient in case 2 was initially misdiagnosed as having an epiphyseal separation of the distal humerus, and open reduction and internal fixation through the posterior approach revealed Milch type II LCF. Interventions: In case 1 and 3, Milch type I LCFs, open reduction and internal fixation was performed through the posterolateral approach. On the other hand, in case 2, Milch type II LCF, open reduction and internal fixation was performed through the posterior approach. Outcomes: Poor reduction of Milch type I LCFs resulted in incongruity of the articular surface and poor cosmetic results in two patients. In case 2, Milch type II LCF, plain radiographs showed adequate healing without elbow deformity and the clinical result was excellent. Lessons: Because LCFs are intra-articular fractures, anatomical reduction is crucial for satisfactory outcomes. We promote awareness of this injury, especially posteromedial dislocation with Milch type I LCF. Preoperative evaluation is helpful for achieving satisfactory outcomes, and open reduction and internal fixation through an anterolateral approach might be most appropriate for Milch type I LCFs.